Sierra Leone : Economic Development Documents-National Development Plan, 2019-23 - International Monetary Fund. African Dept. (2019)
The Government of Sierra Leone’s new Medium-term National Development Plan (MTNDP) 2019–2023 has been founded on a strong political commitment to deliver devel-opment results that would improve the welfare of Sierra Leone’s citizens. The plan charts a clear path towards 2023 en route to the goal of achieving middle-income status by 2039 through inclusive growth that is sustainable and leaves no one behind. For the next five years, the Free Quality School Education Programme is the government’s flagship programme to provide a solid base to enhance human capital development and to facilitate the transformation of the economy.
9781498324960/1934-7685 KerkoCite.ItemAlsoKnownAs: 2405685:DJ4XD4HB

Sierra Leone Multiple Indicator Cluster Survey 2017 - Statistics Sierra Leone (Statistics Sierra Leone, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:7794TCGJ 2405685:N9SALPUS

The Sierra Leone Teachers Union: Labor in a Post-Conflict Society - Amman, John; O'Donnell, James (WorkingUSA, 2011)
The Sierra Leone Teachers Union (SLTU) has long played an important role in the country's education system and its labor movement. With more than 30,000 members, the SLTU is the largest and perhaps the most powerful union in Sierra Leone today. Nonetheless, the union struggles with challenges unheard of in developed countries. It represents teachers in an education system that was ravished by its eleven-year civil war (1991 to 2002). Not only are working conditions extremely difficult for teachers (classroom overcrowding, lack of educational materials, low pay, and often late pay), the union must negotiate union agreements with the Ministry of Education, which itself has no direct influence on the nation's coffers. Sierra Leone's Ministry of Finance and more importantly, the International Monetary Fund set policies that directly impact the quality of Sierra Leone's education system and its teachers.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/j.1743-4580.2011.00320.x KerkoCite.ItemAlsoKnownAs: 10.1111/j.1743-4580.2011.00320.x 2405685:K8W49AUJ

Sierra Leone invests $1.5 million to bring education innovation to schools for better learning outcomes - Sierra Leone Education Innovation Challenge (2019)
A national education dashboard released last month by Sierra Leone’s agency for technology and innovation and the Ministry of Basic and Senior Secondary Education (MBSSE) showed that schools and studentsRead More
Library Catalog: www.dsti.gov.sl EdTechHub.ItemAlsoKnownAs: 2405685:XUALMEQ5

Sierra Leone turns to technology and analytics to put quality back into education - Directorate of Science, Technology & Innovation (Sierra Leone) (2019)
Today, an estimated 2 million students return to school for the second year of the Free Quality School Education (FQSE) Program. The Government of Sierra Leone commits 21% of theRead More
Library Catalog: www.dsti.gov.sl KerkoCite.ItemAlsoKnownAs: 2405685:Z3DPRDU6

‘Without Education You Can Never Become President’: Teenage Pregnancy and Pseudo-empowerment in Post-Ebola Sierra Leone - Menzel, Anne (Journal of Intervention and Statebuilding, 2019)
This article analyses the emergence of ‘teenage pregnancy’ as a new policy focus in post-Ebola Sierra Leone and explores how Sierra Leoneans interpret the problem of ‘teenage pregnancy’. I argue that the new policy focus is not indicative of changing or new problems. Rather, ‘teenage pregnancy’ has created opportunities for donors and the Government of Sierra Leone to continue cooperation in gender politics. At the same time, Sierra Leoneans are clearly concerned about ‘teenage pregnancy’, and many agree with sensitization campaigns that responsibilize young women and girls while downplaying structural factors that render them vulnerable to arrangements involving transactional sex.
Publisher: Routledge _eprint: https://doi.org/10.1080/17502977.2019.1612992 KerkoCite.ItemAlsoKnownAs: 10.1080/17502977.2019.1612992 2405685:MKDQ3K53
Keywords: Sierra Leone; aid and development; gender politics; neoliberalism; sexual violence; teenage pregnancy

Does living in a community with more educated mothers enhance children's school attendance? Evidence from Sierra Leone - Kamanda, Mamusu; Madise, Nyovani; Schnepf, Sylke (International Journal of Educational Development, 2016)
In Sierra Leone girls are 23.4% less likely to attend secondary education than boys. This difference between sexes increases the gender gap in educational attainment since women's education is positively associated with children's educational wellbeing. This paper investigates the relationship between children's school attendance, their mothers’ level of education, as well as the overall level of women's education at the community level in Sierra Leone using multilevel statistical modelling techniques and the country's 2008 Demographic and Health Survey data. The findings suggest that, regardless of a child's own mother's education, an increase in the proportion of mothers with secondary or higher education in a community by 10% improves the probability of attending junior secondary school significantly by 8%; a 50% increase improves the likelihood of attending school by 45%. There was no significant relationship between the proportion of better educated mothers in a community and primary school attendance. However, relative to children whose mothers had no formal education, children whose mothers had attained primary, secondary or higher education were 7%, 14% and 22% more likely to attend primary school respectively. Future policies should seek to promote girls’ education at post-primary education and develop community based programmes to enable the diffusion and transmission of educational messages.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2015.09.008 2405685:YPUYEULY
Keywords: Girls’ education; Mothers’ education; School attendance; Sierra Leone

Understanding Sierra Leonean and Liberian teachers’ views on discussing past wars in their classrooms - Shepler, Susan; Williams, James H. (Comparative Education, 2017)
Various curricular and textbook initiatives exist to aid in the national processes of coming to terms with past violence, often serving the political goals of the victors, sometimes supported by international transitional justice institutions. Sierra Leone and Liberia each experienced a devastating civil war during the 1990s and into the 2000s, and each is struggling to rebuild shattered education systems. In addition, each country has experienced a set of post-conflict transitional justice initiatives: Truth and Reconciliation Commissions in each, and a Special Court for Sierra Leone. Although their respective ministries of education have attempted to address peace education through UNICEF-sponsored curriculum revision processes, those efforts have not yet reached the majority of serving teachers, so a discussion of teachers’ actual practices is vital. This article uses interviews with teachers in rural and urban Sierra Leone and Liberia to discuss whether and how teachers talk about past war in their classrooms; whether they think it is important to discuss past conflicts, and if so, why; and what kind of curricular support would help them better teach about the wars. The article discusses how and why teachers embrace or subvert official efforts through their classroom practices, and compares the Sierra Leone and Liberia contexts and results. This research will help us to understand teachers’ own perspectives on addressing past conflict in their classrooms, and perhaps help policy-makers better implement their peace education initiatives.
Publisher: Routledge _eprint: https://doi.org/10.1080/03050068.2017.1338641 KerkoCite.ItemAlsoKnownAs: 10.1080/03050068.2017.1338641 2405685:9FVX5LB3
Keywords: Education; Liberia; Sierra Leone; teachers; teaching about conflict; transitional justice

Sierra Leone Multiple Indicator Cluster Survey 2017, survey findings report - Statistics Sierra Leone (Statistics Sierra Leone, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:SMX372XG 2405685:EP6QPCSW

Sierra Leone Medium Term National Development Plan (Volume 1) - Ministry of Planning and Economic Development (Sierra Leone) (2019)
EdTechHub.ItemAlsoKnownAs: 2405685:CZE9NFVC

Sierra Leone designs online portal to take long wait out of teacher recruitment - Directorate of Science, Technology & Innovation (Sierra Leone) (2019)
A new teacher recruitment portal developed at the Directorate of Science, Technology, and Innovation (DSTI) will make it easier and faster for education administrators to hire teachers, and allocate teachersRead More
Library Catalog: www.dsti.gov.sl KerkoCite.ItemAlsoKnownAs: 2405685:UWP4N7FT

Sierra Leone 2015 population and housing census: Thematic report on poverty and durables - Statistics Sierra Leone (Statistics Sierra Leone, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:YKBEPH82 2405685:MPV2GIIW

Sierra Leone invests $1.5 million to bring education innovation to schools for better learning outcomes - DSTI Media (Directorate of Science, Technology and Innovation, 2019)
A national education dashboard released last month by Sierra Leone’s agency for technology and innovation and the Ministry of Basic and Senior Secondary Education (MBSSE) showed that schools and studentsRead More
KerkoCite.ItemAlsoKnownAs: 2405685:B6TMDRUY

Redesigning an education project for child friendly radio: a multisectoral collaboration to promote children’s health, education, and human rights after a humanitarian crisis in Sierra Leone - Barnett, Sarah; van Dijk, Jetske; Swaray, Abdulai; Amara, Tamba; Young, Patricia (BMJ, 2018)
Sarah Barnett and colleagues describe how an educational project was rapidly adapted into a radio education programme after the 2014 Ebola epidemic in Sierra Leone
shortDOI: 10/ggqvr7 KerkoCite.ItemAlsoKnownAs: 10.1136/bmj.k4667 10/ggqvr7 2339240:6IXLT92N 2405685:6Z36JH5J 2405685:S35X3HD9

Sierra Leone’s Medium-Term National Development Plan 2019-2023: Education for Development. - Government of Sierra Leone (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:RPKBXC8H 2405685:XNWLCKWJ

Digital School Census in 10 Weeks? How it was done in Sierra Leone - Namit, Kariba; Mai, Thanh Thi (World Bank Blogs, 2019)
Note: This blog is specifically about Sierra Leone’s successful transition to a digital school census but has broader implications for other countries who plan to adopt digital tools at a wider scale to collect data and monitor education and healthcare facilities in their countries. In April of last year, the new Minister of Finance of Sierra Leone approached the World Bank with a strong commitment to prioritize education and an intriguing request.
Library Catalog: blogs.worldbank.org KerkoCite.ItemAlsoKnownAs: 2339240:PP5768J6 2339240:TGTJZWCC 2405685:EPMH5GMB 2405685:EY9VEBRN 2405685:KXNLTUXL 2405685:NUSFD2XU 2405685:PLIT3YBG 2405685:TIEFATQQ 4803016:S4RTD2LL

Sierra Leone 2015 Population and Housing Census: Thematic Report on Disability - Kabia, Francis; Tarawally, Umaru (Statistics Sierra Leone, 2017)
KerkoCite.ItemAlsoKnownAs: 2405685:BI8HMKXI

Sierra Leone: Education Country Status Report: An analysis for further improving the quality, equity and efficiency of the education system in Sierra Leone - Ministry of Education, Science and Technology (Government of Sierra Leone, 2013)
KerkoCite.ItemAlsoKnownAs: 2405685:FWX5GT4H

Education Sector Plan, 2018-2020: Getting It Right – Service Delivery, Integrity and Learning in Sierra Leone - Ministry of Education, Science and Technology (Government of Sierra Leone, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:AIISD4KD 2405685:DFHS5ZVL

The teacher salary system in Sierra Leone - Turrent, Victoria (2012)
KerkoCite.ItemAlsoKnownAs: 2129771:57MI994B 2129771:EDZ7UPYF 2339240:HPKYUKLY 2339240:K8K3HH88 2405685:JYDRFRHV 2405685:LR6N966K 2405685:YMKMBLNW 2486141:5RFTC82M 4556019:2UB9U5R4
Keywords: C:Sierra Leone; _C:Sierra Leone SLE; ⛔ No DOI found

The Agenda for Prosperity: Road to Middle Income Status - Government of Sierra Leone (2013)
KerkoCite.ItemAlsoKnownAs: 2339240:FHMH4G7H 2405685:7DIVY6PP
Keywords: ⛔ No DOI found

Sierra Leone National Innovation and Digital Strategy (2019-2029). Digitization for all: Identity, Economy, and Governance - Directorate of Science, Technology & Innovation (Government of Sierra Leone, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:Q6QR6YET 2339240:Q8HXYPXT 2339240:ZAK6UTWJ 2405685:65CSGZUZ 2405685:ALD9DQ6P 2405685:GWCHFY72 2405685:XG7MKFV5

Proposal to the Global Partnership for Education for a contribution towards the implementation of the 2018-2020 Education Sector Plan - Ministry of Education, Science and Technology (Sierra Leone) (2018)
EdTechHub.ItemAlsoKnownAs: 2405685:GVAZB6TM

Education Sector Plan 2018-2020 - Ministry of Education, Science and Technology (Sierra Leone) (2018)
EdTechHub.ItemAlsoKnownAs: 2405685:24PRFKEK

Donor policies in post-war Sierra Leone - Kanyako, Vandy (Journal of Peacebuilding & Development, 2016)
The Sierra Leone peace process following the country's 1991–2002 civil war between the Government of Sierra Leone (GoSL) and the Revolutionary United Front (RUF) benefited immensely from the energetic involvement of an eclectic mix of donors. Traditional inter-governmental financial institutions and relatively new private funding foundations all channelled aid money and technical expertise through various multilateral and bilateral mechanisms for rebuilding the country. Without a doubt Sierra Leone's recovery from the debilitating 11-year war would not have come to pass in the time and manner it did without the robust intervention of such funders. Based on fieldwork conducted in Sierra Leone at the height of the peacebuilding process, this article outlines the role played by international donors in rebuilding post-war Sierra Leone. It posits that understanding the modus operandi of the assorted mix of donor agencies in creating the country's aid architecture is key to grasping the nuances of the Sierra Leone peace process. This is partly because the aid largesse, though well intentioned, was injected into a barely functioning system that lacked a coherent recipient regime. The article concludes that though donors were critical to Sierra Leone's rebuilding efforts, their lack of emphasis on a needs-centred funding mechanism created an inadequate model to address the country's complex post-war reconstruction challenges.
Publisher: SAGE Publications Inc KerkoCite.ItemAlsoKnownAs: 10.1080/15423166.2016.1146035 2339240:EC6LW5LV 2405685:IHKCCGSR

National Education Policy - Ministry of Education, Youth and Sports (Sierra Leone) (2010)
KerkoCite.ItemAlsoKnownAs: 2405685:YLXI3EW2

Digital School Census in 10 Weeks? How it was done in Sierra Leone - Namit, Kariba; Mai, Thanh Thi (World Bank Blogs, 2019)
Note: This blog is specifically about Sierra Leone’s successful transition to a digital school census but has broader implications for other countries who plan to adopt digital tools at a wider scale to collect data and monitor education and healthcare facilities in their countries. In April of last year, the new Minister of Finance of Sierra Leone approached the World Bank with a strong commitment to prioritize education and an intriguing request.
KerkoCite.ItemAlsoKnownAs: 2405685:BFZ3FTAT 2486141:G289KIHC

Sierra Leone Media Landscape Report - BBC Media Action (2018)
KerkoCite.ItemAlsoKnownAs: 2339240:7N6UW9TG 2405685:644SZI8D

Reconstructing education in post-conflict Sierra Leone - Pai, Grace (Security, Education and Development in Contemporary Africa, 2016)
KerkoCite.ItemAlsoKnownAs: 2405685:83TRVQZR

Education in Emergencies Endline Evaluation Report – Sierra Leone - Sankoh, Didan; Cowan, Emma (Girls' Education Challenge, UK Aid, 2016)
KerkoCite.ItemAlsoKnownAs: 2405685:G2I2A3Y5

Disability in and Around Urban Areas of Sierra Leone - Trani, Jean-Francois; Bah, Osman; Bailey, Nicki; Browne, Joyce; Groce, Nora; Kett, Maria (2017)
KerkoCite.ItemAlsoKnownAs: 2405685:FSQFJ72I

Project Information Document (PID): Sierra Leone Free Education Project (P167897) - World Bank (World Bank Group, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:6FWAUCW5 2405685:XAKZSJBD

Sierra Leone research and knowledge systems: a rapid literature review - Tarawallie, Mamoud Idriss (INASP, 2015)
KerkoCite.ItemAlsoKnownAs: 2339240:83QNDI62 2405685:8PAQ6CIE

Developing Inclusive Education Policy in Sierra Leone: A Research Informed Approach - Rose, R.; Garner, P.; Farrow, B. (Inclusion, Equity and Access for Individuals with Disabilities., 2019)
https://doi.org/10.100/ 978-981-13-5962-0_21 KerkoCite.ItemAlsoKnownAs: 2405685:AMF2AQAE

Open Data Readiness Assessment: Prepared for the Government of Sierra Leone - Chrzanowski, Pierre; Holm, Jeanne; Manley, Laura; Dodds, Elizabeth; Baker, Rob (World Bank Group; Open Aid Partnership, 2016)
KerkoCite.ItemAlsoKnownAs: 2405685:83I8VUFY

Republic of Sierra Leone Higher and Tertiary Education Sector Policy Note - World Bank (2013)
KerkoCite.ItemAlsoKnownAs: 2339240:ANFH2ALH 2405685:QAFBTUE9

Successes and challenges of implementing a teacher education project in rural Sierra Leone - Mcdermott, Peter; Allen, Nancy (International Journal of Educational Research, 2015)
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijer.2015.02.001 2405685:8F6MKJP5

Devising New Models for School Improvement in Developing Nations: Sierra Leone, a case study - Mason, Miriam Theresa (Durham University, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:55RYBL9Q

A Skills Gap Analysis for Private Sector Development in Sierra Leone 2012 Economic Sector Work - Mannah, Emmanuel; Ngadi Gibril, Yvonne (2012)
KerkoCite.ItemAlsoKnownAs: 2405685:RFM2MVCL

GSMA Mobile Connectivity Index | Sierra Leone - GSMA (2018)
The GSMA Mobile Connectivity Index is a global mobile connectivity and digital economy guide covering 150 countries and 7 sub-regions
Library Catalog: www.mobileconnectivityindex.com EdTechHub.ItemAlsoKnownAs: 2405685:AGNKXIPC

Sierra Leone Multiple Indicator Cluster Survey - UNICEF (2017)
KerkoCite.ItemAlsoKnownAs: 2405685:6T7FE548

Using examination and learning assessment data to uncover foundational skill gaps in Sierra Leone’s secondary schools - Waistell, Daniel; De, Sourovi; Ofori Owusu, Diana; Allen, Reg; Sanni, Kayode; Dupigny, Albert (Education technology and data science for inclusive systems, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:J8IWHLVQ
Keywords: ⛔ No DOI found

Sierra Leone: Transforming the Country through Innovation - O'Connor, Shane; Zurutuza, Naroa (UNICEF, 2019)
Library Catalog: www.unicef.org KerkoCite.ItemAlsoKnownAs: 2405685:XYSCRRC4

Project Information Document: Sierra Leone Free Education Project - World Bank (2019)
EdTechHub.ItemAlsoKnownAs: 2405685:GIC5MV46

Revitalizing Education Development in Sierra Leone (REDISL) Project - World Bank (2014)
KerkoCite.ItemAlsoKnownAs: 2405685:8ISYUKP9

It takes a village to raise a teacher: the Learning Assistant programme in Sierra Leone - Crisp, Martin; Wolfenden, Freda (2017)
KerkoCite.ItemAlsoKnownAs: 2405685:I76Z2SKV

A Comprehensive Situation Analysis of Teachers and the Teaching Profession in Sierra Leone: Final report presented to the Teaching Service Commission - Wright, Dr. Cream (Global Partnership for Education; World Bank, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:9VRVIUE6 2405685:UU3R28HB

Ebola, Education And Innovation In Sierra Leone - Berry, Chris (DFID bloggers, 2015)
KerkoCite.ItemAlsoKnownAs: 2339240:Y4SENBBT 2405685:CYLG6GK7 2405685:DD7BMIBU
Keywords: ___working_potential_duplicate

Final Evaluation of the Project: Increasing Access, Retention and Performance in Primary Education: Implemented by Child to Child & the Pikin-To-Pikin Movement Kailahun District, Sierra Leone, 2011-2016 - Institute for Development (2016)
KerkoCite.ItemAlsoKnownAs: 2339240:3E624NH3 2405685:5LVXNGJZ 2405685:CRQUMLFF

Education Needs Assessment Report - Sierra Leone - Plan International (2016)
KerkoCite.ItemAlsoKnownAs: 2405685:FPBLY982 2486141:T8M7TVMD

Open Government Case Study: Costing Sierra Leone’s Open Data Program - Joswiak, Naomi (Results for Development, 2017)
KerkoCite.ItemAlsoKnownAs: 2405685:AN5GA9QR
Keywords: ___working_potential_duplicate

Technology and Teacher Professional Development (TPD): the Process and Content of Microlearning in a School-Based Integrated In-Service Teacher Education (INSET) Project - Junaid, Muhammad Ibn; Ogange, Betty; Allela, Melisa (Commonwealth of Learning (COL), 2019)
Continuing teacher professional development for all teachers across the entire school system poses a challenge in many contexts, especially in developing countries. Teachers from schools located in remote rural areas usually have fewer professional development opportunities due to the lack of accessibility either to their schools or to professional development resources. On-site school-based professional development is a viable option if innovative design is adapted to generate microlearning resources that teachers can easily access and share. This paper reports on a technology enabled school-based integrated INSET project coordinated by the Freetown Teachers College (FTC) in 12 junior secondary schools (JSS) in Sierra Leone under the COL’s Teacher Futures Programme. The project represents an innovation in TPD and is different from the general type of face-to-face and exclusively paper-based in-service teacher training programme common in Sierra Leone. Under the new project a multimodal approach is used where the FTC mentors and the communities of learners (JSS teachers) are presented with both print and microlearning resources and also provided access to an eLearning platform and the use of mobile phones as the main vehicles of delivery. Microlearning is an emergent learning strategy known for its quick response in bridging skills and knowledge gaps. In the context of the INSET Project, it involves a weekly dose of pedagogical content knowledge and skills, including modelling of classroom best practices which teachers can adapt and use. The project design and methods are briefly described, but the main focus of the paper is on the microlearning component of this project and discusses the use of mobile technology in the delivery and implementation of TPD in the 12 project schools. The emphasis is on the methodological and management challenges that arise in creating and nurturing communities of practice (CoPs) in a school-based setting and how these are addressed by the various schools involved.
KerkoCite.ItemAlsoKnownAs: 2405685:AALEIRC2

2019 Annual Schools Census Report And Statistical Abstract - Ministry of Basic and Senior Secondary Education (Government of Sierra Leone, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:MJH7EBNP 2405685:VM4EWGLU

FQSE – Free Quality School Education - Ministry of Basic and Senior Secondary Education Sierra Leone (Ministry of Basic and Senior Secondary Education Sierra Leone, Government of Sierra Leone, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:XL83AVZI 2405685:7NLKWES7

Sierra Leone Teaching Service Commission Act - Government of Sierra Leone (2011)
KerkoCite.ItemAlsoKnownAs: 2339240:XVKYXQ4E 2405685:D8ZBENA6

Keynote Address by His Excellency President Julius Maada Bio on the theme of: "Education for Development" at the launch of the Free Quality School Education Programme - Maada Bio, Julius (2018)
KerkoCite.ItemAlsoKnownAs: 2339240:5TSMLUKK 2405685:FW7MT9FE

What makes a good classroom? New UIS data on school conditions - UNESCO (UNESCO, 2019)
New data from the UNESCO Institute for Statistics (UIS) reveal serious disparities in the schooling conditions facing children and teachers – from access to electricity, clean drinking water and single sex-toilets to Internet access and computers. Classroom conditions are key in providing a quality education for all. For children who struggle to enrol in school, for example due to poverty or discrimination on the grounds of gender or disability, poor school conditions can further undermine their chances of a quality education. What are the new data looking at?
KerkoCite.ItemAlsoKnownAs: 2339240:4DRK8RBZ 2405685:PT5I7FT5

Continental Education Strategy For Africa (2016 – 2025) - African Union (2016)
KerkoCite.ItemAlsoKnownAs: 2405685:EH4P26FW

Education for sustainable development in Africa: a critique of regional agendas - Tikly, Leon (Asia Pacific Education Review, 2019)
Education is often perceived in policy agendas as playing a transformative role in realising sustainable development and the SDGs on the continent. The assumption is based, however, on an insufficiently critical understanding of the historical role of education in supporting unsustainable development. The article provides a critical account of the relationship between education policy and sustainable development in Africa as an aspect of the postcolonial condition, i.e. as an aspect of the colonial legacy and of Africa’s position in relation to contemporary processes of globalisation. It is argued that if education is to play a transformative role in relation to sustainable development then education policy needs to be fundamentally re-oriented and harnessed to wider processes of economic, cultural and political transformation in the interests of social and environmental justice.
KerkoCite.ItemAlsoKnownAs: 10.1007/s12564-019-09600-5 2405685:UUXGULFV

Ethiopia Growth and Transformation Plan II (GTP II) | Green Growth Knowledge Platform - Ethiopia National Planning Commission (Federal Democratic Republic of Ethiopia, 2016)
KerkoCite.ItemAlsoKnownAs: 2405685:XG2MRXIK

Sierra Leone population 2020 - WorldPop (2018)
RF-based gridded population distribution datasets produced in the framework of the Global Project - Funded by The Bill and Melinda Gates Foundation (OPP1134076)
KerkoCite.ItemAlsoKnownAs: 10.5258/SOTON/WP00645 2339240:2AJ3LMLD 2405685:92787LQS
Keywords: Population distribution; Population; Dasymetric disaggregation

Open Data Readiness Assessment: Sierra Leone - World Bank (2015)
KerkoCite.ItemAlsoKnownAs: 2339240:GHD8WBJM 2405685:5GLY6KEA

Government of Sierra Leone Education Data Hub - Directorate of Science, Technology and Innovation (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:8BAXTEYI 2405685:46EQS5JF

Sierra Leone - Multiple Indicator Cluster Survey 2017 - World Bank (2017)
KerkoCite.ItemAlsoKnownAs: 2339240:693W742X 2405685:4ULW3LMX

Education for Development - Maada Bio, Julius (2018)
KerkoCite.ItemAlsoKnownAs: 2405685:KL7FDUU7

Proportion of schools with access to basic facilities, all schools - UNESCO (2018)
EdTechHub.ItemAlsoKnownAs: 2405685:ZV8MELAV

Mobile Learning Lab Evaluation & Analysis - 60 Million Girls (60 million girls, 2018)
Library Catalog: 60millionsdefilles.org EdTechHub.ItemAlsoKnownAs: 2405685:ZPG2W382

Leh Wi Learn - Sierra Leone Secondary Education Improvement Programme - DFID (2018)
KerkoCite.ItemAlsoKnownAs: 2405685:9PJP3ZYU

Sierra Leone: Economic Development Documents-National Development Plan, 2019-23 - International Monetary Fund (IMF, African Department, 2019)
ISBN: 9781498324960 ISSN: 1934-7685 Issue: 218 Publisher: INTERNATIONAL MONETARY FUND Volume: 2019 KerkoCite.ItemAlsoKnownAs: 10.5089/9781498324960.002.A001 2339240:6RP4BCNR 2405685:LICLRGV3

Automated teller machines (ATMs) (per 100,000 adults) - Sierra Leone - World Bank (2012)
KerkoCite.ItemAlsoKnownAs: 2129771:EERHMIDA 2405685:IECJPUES 4556019:QB8DZSFF

Teachers and the Teaching Profession in Sierra Leone: A comprehensive situation analysis - Wright, Cream (Teaching Service Commission, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:BPP6QJJT 2405685:K3L9HBBP 2405685:S8XYIRCN 2486141:4XFKHYLJ 2601447:KDYSFZB9

A longitudinal study of learning, progression, and personal growth in Sierra Leone - Johnson, David; Hsieh, Jenny (University of Oxford, 2019)
EdTechHub.ItemAlsoKnownAs: 2405685:A2EVGSWW

Open Government Case Study: Costing Sierra Leone’s Open Data Program - Joswiak, Naomi (Results for Development, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:ZNYWJ9PF 2405685:7HSIXMSV
Keywords: ___working_potential_duplicate

The permanent input hypothesis : the case of textbooks and (no) student learning in Sierra Leone - Sabarwal, Shwetlena; Evans, David K.; Marshak, Anastasia (Washington, DC : World Bank, Education Global Practice Group & Africa Region, Office of the Chief Economist, 2014)
KerkoCite.ItemAlsoKnownAs: 2405685:QFBK2Z4L

Incidence of malaria (per 1,000 population at risk) - Sierra Leone, Sub-Saharan Africa (excluding high income) | Data - World Bank (2018)
KerkoCite.ItemAlsoKnownAs: 2129771:6RCWKTSF 2405685:7HILUDQR 4556019:XR5GKQEB

A Comprehensive Situation Analysis of Teachers and the Teaching Profession in Sierra Leone: Final report presented to the Teaching Service Commission - Teaching Service Commission (Global Partnership for Education, 2018)
KerkoCite.ItemAlsoKnownAs: 2405685:CFRE6D4Q

Understanding the Barriers and enablers of Effective Communities of Practice in Sierra Leone Through a Collaboration Between Dubai Cares and Open Development and Education - Lurvink, Anne-Fleur (Open Development & Education, 2019)

The Economic Lives of Young Women in the Time of Ebola: Lessons from an Empowerment Program - Bandiera, Oriana; Buehren, Niklas; Goldstein, Markus; Rasul, Imran; Smurra, Andrea (World Bank, 2018)
We evaluate an intervention to raise young women’s economic empowerment in Sierra Leone, where women frequently experience sexual violence and face multiple economic disadvantages. The intervention provides them with a protective space (a club) where they can …nd support, receive information on health/reproductive issues and vocational training. Unexpectedly, the post-baseline period coincided with the 2014 Ebola outbreak. Our analysis leverages quasi-random across-village variation in the severity of Ebola-related disruption, and random assignment of villages to the intervention to document the impact of the Ebola outbreak on the economic lives of 4 700 women tracked over the crisis, and any ameliorating role played by the intervention. In highly disrupted control villages, the crisis leads younger girls to spend signi…cantly more time with men, out-of-wedlock pregnancies rise, and as a result, they experience a persistent 16pp drop in school enrolment post-crisis. These adverse e¤ects are almost entirely reversed in treated villages because the intervention enables young girls to allocate time away from men, preventing out-of-wedlock pregnancies and enabling them to re-enrol in school post-crisis. In treated villages, the unavailability of young women leads some older girls to use transactional sex as a coping strategy. The intervention causes them to increase contraceptive use so this does not translate into higher fertility. Our analysis pinpoints the mechanisms through which the severity of the aggregate shock impacts the economic lives of young women, and shows how interventions in times of crisis can interlink outcomes across younger and older cohorts. JEL Classi…cation: I25, J13, J24.
shortDOI: 10/ghgngq KerkoCite.ItemAlsoKnownAs: 10.1596/1813-9450-8760 10.1596/31219 10/ghgngn 10/ghgngq 2339240:P9QQ2FKF 2405685:2TEE6A8C 2405685:BA7ISGH3
Keywords: ___working_potential_duplicate

Proposal to the Global Partnership for Education for a contribution towards the implementation of the 2018-2020 Education Sector Plan - Ministry of Education, Science and Technology (Government of Sierra Leone; UNICEF, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:843DCCS6 2405685:HZ89SJYF

2019 Annual School Census Report - Ministry of Basic and Senior Secondary Education (Ministry of Basic and Senior Secondary Education, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:99GBVUWP 2339240:NBI2YGW4 2405685:PF3NKF32 2405685:QNZEXSV3 2405685:SK6ZDI63 2486141:IVGKRIEH

10 principles to consider when introducing ICTs into remote, low-income educational environments - Trucano, Michael (World Bank Blogs, 2013)
there must be an I, a C, and a T here somewhere ... There are, broadly speaking, two strands of concurrent thinking that dominate discussions around the use of new technologies in education around the world. At one end of the continuum, talk is dominated by words like 'transformation'. The ...
Library Catalog: blogs.worldbank.org KerkoCite.ItemAlsoKnownAs: 2339240:5I5XNP44 2339240:7ENMXVAZ 2339240:7TDXW2WT 2339240:M7NFMPY5 2405685:23SM2GHY 2405685:2KLF59UJ 2405685:4QHLLY7H 2405685:BJSJWEMM 2405685:EJG6JBSL 2405685:EY7WAUHY 2405685:MDR3XLXP 2405685:N584ISNZ 2405685:RCHYAVL3 2405685:SVDWLWHS 2405685:XED3H9S7 4042040:MXSNKXZ5 4656463:P4BDEDD3 4656463:YXDWWIE2

Country list with HDI, iHDI, MPI and Gini (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
This is pdf of a country list with HDI, iHDI, MPI and Gini. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB (which will also be available as a data file).
previousshortDOI: 10/ghgk6v previousDOI: 10.5281/zenodo.3346903 EdTechHub.Source: 2405685:3BG5X7VG EdTechHub.Source: <this> shortDOI: 10/ghgk6v KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3346903 10.53832/edtechhub.0017 10/ghgk6v 2129771:FLGEYF22 2339240:SZ4GSDD6 2405685:3BG5X7VG
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:q; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Mission and Vision - Ministry of Technical & Higher Education (Ministry of Technical & Higher Education Republic of Sierra Leone, Government of Sierra Leone, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:PM4PUYXJ 2405685:LI99LYJA

Keyword inventory (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
The document contains the keyword inventory used for automated searching. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB.
previousshortDOI: 10/ghgnfm previousDOI: 10.5281/zenodo.3523935 EdTechHub.Copy: 2129771:NB3WMPDJ shortDOI: 10/ghgnfm KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3523935 10.53832/edtechhub.0016 10/ghgnfm 2129771:NB3WMPDJ 2339240:B5AIHWDZ 2405685:2GC35JLV 2405685:LSEETV6K
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:p; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Statement from the Minister - Ministry of Technical & Higher Education (Ministry of Technical & Higher Education, Government of Sierra Leone, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:QIYCJQ6B 2405685:7G2FJMLB

Sustaining and scaling pedagogic innovation in sub-Saharan Africa: Grounded insights for teacher professional development - Haßler, Björn; Hennessy, Sara; Hofmann, Riikka (Journal of Learning for Development, 2018)
Developing sustainable and scalable educational initiatives is a key challenge in low-income countries where donor-funded short-term projects are limited by both contextual factors and programme design. In this concept paper we examine some of the issues related to in-service teacher development in the context of sub-Saharan Africa, grounded predominantly in our experiences of over 5 years of iteratively developing, refining and evaluating an intensive school-based professional learning programme for primary school teachers. “OER4Schools” integrates interactive pedagogy, Open Educational Resources (OER) and use of mobile devices (where available). The focus of this paper is on identifying what the main factors are perceived to be in sustaining and scaling up such a programme, from the perspectives of participating teachers, workshop facilitators and the research team. Synthesising our previous research and drawing on recent work in the field, we identify the key characteristics of effective and sustainable professional learning in low-resourced contexts. Such characteristics include effective peer facilitation, school-based active learning, explicit programme structure, appropriate scheduling and resourcing, and mitigating resource constraints through use of OER. Our conclusions thereby offer insights concerning the importance and impact of wider influences on participation and engagement of stakeholders and lead to recommendations for programme design and implementation, that should be taken on board by future initiatives.
00000 EdTechHub.Source: 2129771:D2GQYC5S KerkoCite.ItemAlsoKnownAs: 10.56059/jl4d.v5i1.264 2129771:43ZT3XWL 2129771:52KKAHKR 2129771:AAT7FR3H 2129771:D2GQYC5S 2129771:LDWSNI7T 2129771:LHMXV7QF 2249382:CS9PALG8 2317526:6IH7CD39 2317526:PP4CHVEG 2339240:2BCABLG6 2339240:4N3G4XDJ 2339240:9BPXVI62 2339240:C7CKIPL7 2339240:D83N6FTA 2339240:HGHAYJ5G 2339240:HR2YGWX3 2339240:P65I7MGU 2339240:YSVITTWH 2405685:3GSCKVWC 2405685:7X2D9JDG 2405685:CUHYHFLV 2405685:M8UDHT7A 2405685:NKSYKNQN 2405685:NVEVT9HX 2405685:NZ3GKZCR 2405685:T2I86FZT 2405685:ZFJ79LQS 2486141:Z3PRLX4K 257089:AJJPQKDF 261451:JC3NQMN3 261495:BWD9L8FL 261495:TCP47GGI
Keywords: AWP2; Active Learning; Africa; Author:Haßler; C:sub-Saharan Africa; CitedIn:DFID_SRF; CitedIn:OER4S-TPE-Anon; CitedIn:OER4Schools-2012-HHH1-anon; CitedIn:PhD_Thesis; DIAL-RDO; Developing Nations; Educational Technology; Elementary Secondary Education; Faculty Development; Foreign Countries; Handheld Devices; IMPORT_FROM_DFID_RITE; InPrep; Inservice Teacher Education; Low Income Groups; Motivation; OER4Schools; Open Educational Resources; Peer Teaching; RPF-May-2016; Resource Allocation; Rural Schools; Scaffolding (Teaching Technique); Scheduling; Shared Resources and Services; Sustainable Development; Sustainable Development Goal 4; Teacher Professional Development; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; dode_eth-src-dode; dode_eth-trf2-dode; missingHU; peer-facilitation; school-based active learning; sub-Saharan Africa; ⛔ No DOI found

Tablet use in schools: a critical review of the evidence for learning outcomes - Haßler, Björn; Major, Louis; Hennessy, Sara (Journal of Computer Assisted Learning, 2016)
EdTechHub.Source: 2129771:9IYKEUKJ shortDOI: 10/f8f6mc KerkoCite.ItemAlsoKnownAs: 10.1111/jcal.12123 10/f8f6mc 2129771:6YGVDBXS 2129771:9IYKEUKJ 2129771:BFWTG2BG 2129771:HX6DBG7W 2317526:3V7LV2NP 2339240:C6LDZSDW 2339240:GNBA7ZJI 2339240:WPK23R37 2339240:YYGY6J8F 2405685:7552P2EL 2405685:9I6F956M 2405685:J6HBWCZL 2405685:SZ2DB7K2 503888:U6FRZHMB
Keywords: Android; Author:Haßler; dode_eth-src-dode; dode_eth-trf2-dode; iPad; learning outcomes; school; systematic reviews; tablets